Comparison of the American-European Consensus Group Sjögren's syndrome classification criteria to newly proposed American College of Rheumatology criteria in a large, carefully characterised sicca cohort. Issue 1 (22nd August 2013) - Rasmussen, Astrid; Ice, John A; Li, He; Grundahl, Kiely; Kelly, Jennifer A; Radfar, Lida; Stone, Donald U; Hefner, Kimberly S; Anaya, Juan-Manuel; Rohrer, Michael; Gopalakrishnan, Rajaram; Houston, Glen D; et al.
Abstract: Objective: To compare the performance of the American–European Consensus Group (AECG) and the newly proposed American College of Rheumatology (ACR) classification criteria for Sjögren's Syndrome (SS) in a well-characterised sicca cohort, given ongoing efforts to resolve discrepancies and weaknesses in the systems. Methods: In a multidisciplinary clinic for the evaluation of sicca, we assessed features of salivary and lacrimal gland dysfunction and autoimmunity as defined by tests of both AECG and ACR criteria in 646 participants. Global gene expression profiles were compared in a subset of 180 participants. Results: Application of the AECG and ACR criteria resulted in classification of 279 and 268 participants with SS, respectively. Both criteria were met by 244 participants (81%). In 26 of the 35 AECG+/ACR participants, the minor salivary gland biopsy focal score was ≥1 (74%), while nine had positive anti-Ro/La (26%). There were 24 AECG−/ACR+ who met ACR criteria mainly due to differences in the scoring of corneal staining. All patients with SS, regardless of classification, had similar gene expression profiles, which were distinct from the healthy controls. Conclusions: The two sets of classification criteria yield concordant results in the majority of cases and gene expression profiling suggests that patients meeting either set of criteria are more similar to other SS participants than to healthy controls. Thus, there is no clear evidence for increased value of the new ACR criteria over the old AECG criteria from the clinical or biological perspective. It is our contention, supported by this report, that improvements in diagnostic acumen will require a more fundamental understanding of the pathogenic mechanisms than is at present available.